Reflecting on an Integrated Approach to Understanding Pathways for Socially Inclusive Agricultural Intensification. Issue 8 (3rd August 2022) - Merritt, Wendy S.; Hamilton, Serena H.; Bagchi, Niladri S.; Baral, Nayana; Carter, Lucy; Chakraborty, Arnab; Chakraborty, Subhankar; Cosijn, Michaela; Das, Mahanambrota; Hossain, Mohammad Ismail; Jahan, Hasneen; Mishra, Pulak; et al.
Abstract: Large investments in Research-for-Development (R4D) have occurred around agricultural intensification to improve social and economic outcomes for poor small and marginal farmer households. Mixed evidence for sustained and socially just impacts from these investments reflects that projects aimed at achieving social change are inherently complex and the pathways from intervention to impact are deeply uncertain. R4D projects are increasingly drawing on integrative approaches to explore solution spaces for these complex social-agroecological problems; albeit integration science is not yet mainstream in R4D. We reflect on one approach (integrated assessment, IA) in a project on socially inclusive agricultural intensification, namely on how the project team embraced integration tools and research approaches, translated knowledge and learnings of the community and broader research team into systems frameworks, and ensured that social inclusion and justice concepts were central to the IA tools and process. IA was valued for its participatory focus and for lessening 'silo thinking' in the design of community interventions and research activities. We argue that complexity-aware integration approaches like IA are needed to support the design, monitoring and evaluation of R4D projects to enhance outcomes and achieve sustained impact.